An annotated checklist of the handsome fungus beetles of the world (Coleoptera: Cucujoidea: Endomychidae) - Shockley, F. W.; Tomaszewska, K. W.; Mchugh, J. V. (Zootaxa, 2009)
A worldwide checklist is provided for the family Endomychidae (Coleoptera: Cucujoidea). An updated subfamilial classification is presented, based on recent higher-level phylogenetic analyses and incorporating many recently described taxa. At present, Endomychidae contains 1782 valid species and subspecies in 130 genera organized into 12 subfamilies. Two new synonyms are recognized: Symbiotes latus Redtenbacher, 1849 = Symbiotes latus var. roberti Falcoz & Roman, 1930 syn. nov.; and Cholovocerida Belon, 1884 = Displotera Reitter, 1887b syn. nov. Two new combinations are proposed: Cholovocerida ecitonis (Wasmann, 1890) for Coluocera ecitonis Wasmann, 1890 comb. nov.; and Cholovocerida maderae (Wollaston, 1854) for Cholovocera maderae Wollaston, 1854 comb. nov. Loeblia ceylanica Dajoz, 1972a is here designated as the type species for Loeblia Dajoz, 1972a, and Rhymbus hemisphaericus Gerstaecker, 1858 is designated as the type species for Rhymbus Gerstaecker, 1858. Nomen nudum status is proposed for Mycetaea tafilaletica Smirnoff, 1957. Thirty-two species originally described under Corynomalus Chevrolat, 1836 and subsequently transferred to Amphix Laporte, 1840, have been returned to Corynomalus. Known fossil taxa are summarized.